Evaluating professional performance of environmental educators - Loret de Mola, E.; Méndez, I. E.; Rivero, M. L. (Transformación, 2013)
The paper is intended to outline criteria for evaluating professional performance of environmental educators by describing dimensions, sub-dimensions and indicators for appraising the professional performance of environmental educators’ variable, controlled by means of a set of tools and statistics techniques. The authors start by presenting a framework dealing with competence and performance in the field of environmental education that allows defining the terms environmental professional training, professional performance of environmental educators, and evaluation of professional performance of environmental educator.